2016
DOI: 10.1177/1534734616667865
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Open Subtotal Calcanectomy and Stabilization With External Fixation as Limb Salvage Procedure in Hindfoot-Infected Diabetic Foot Ulcers

Abstract: Diabetic hindfoot ulcers, complicated by osteomyelitis, are associated with a high risk of major amputation. Partial calcanectomy, preceded by an effective management of the infection and of the eventual peripheral artery disease, can be considered as valid therapeutic option. We have evaluated a therapeutic protocol for diabetic hindfoot ulcers complicated by osteomyelitis, which, besides an adequate surgical debridement, considers a reconstructive pathway assisted by the positioning of a circular external fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…In two studies 15,16, Ilizarov circular frames were used to off-load and maintain the foot in equinus position to decrease the plantar soft tissue defect. In the study by Akurtt et al (2017), they assessed the outcome of 23 patients treated with an Ilizarov frame.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies 15,16, Ilizarov circular frames were used to off-load and maintain the foot in equinus position to decrease the plantar soft tissue defect. In the study by Akurtt et al (2017), they assessed the outcome of 23 patients treated with an Ilizarov frame.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 15,26 reported the use of dermal substitute layers without infection recurrence. However, 20% of the patients needed a skin graft or a second dermal layer implantation due to wound healing disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent advances in antimicrobial therapy ( 6 , 7 ), diabetic foot lesions continue to be a serious problem. Foot ulcer treatments are lengthy, costly and require intensive care ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heel ulcers, a common manifestation in people with diabetes, are often associated with infection or Charcot’s joint disease. When calcaneal ulcers are complicated by osteomyelitis, pressure ankle ulcers or joint deformities and pain caused by Charcot to avoid below-knee amputations, partial calcaneal resection should be considered to remove all necrotic and infected tissue, deformed bone or osteophytes (note that no infected tissue or plantar bone protrusions should be left behind) [ 127 ]. Bone biological materials (BBMs) include bone conduction materials, such as bone grafts, calcium ceramics, hydroxyapatite and collagen and osteoinductive materials, such as platelet gel concentrates, demineralized bone matrix and bone morphogenetic proteins.…”
Section: Management Of Diabetic Footmentioning
confidence: 99%